On the solvability of a mixed problem for partial differential equations of parabolic type with involution - Turmetov, B.; Ahmedov, Anvarjon A.; Orazov, Isabek (IOP Publishing Ltd, 2021)
Mixed partial differential equation of parabolic type with involution is considered. The sufficient conditions of the existence and uniqueness of the solution for the parabolic type equations with involution is obtained. The Fourier method is used to find a classical solution of the mixed problem for the transformed parabolic type equation with involution.